Multi-variable prioritization model for risk evaluation scenarios in mechanical design - Anes, Vitor (2018)
Risk prioritization is an important procedure in FMEA methodology where failure modes are prioritized using the so-called risk priority number (RPN), which prioritizes failure modes based in only three risk variables usually, severity, occurrence, and detectability. However, in some risk scenarios, more than three risk variables can improve risk prioritization, but an ease risk prioritization model like RPN for more than three risk variables cannot be found in literature. We developed a risk prioritization model to prioritize failure modes evaluated with more than three risk variables. The model has the same ease of use found in the traditional risk prioritization number model, but it overcomes its drawbacks. Results show that the risk prioritization made with the proposed model agrees with the expectations made for the risk scenario. Moreover, it was shown that the proposed model is injective, surjective and can prioritize failure modes based on a given order of importance defined by the user. These features show that the major shortcoming found in the conventional risk prioritization were overcome on the proposed model. Our model opens the possibility of traditional FMEA users to use more than three risk variables without the need of prior knowledge, fact that has been the main reason of traditional risk priority number popularity, despite its strong shortcomings.